2019
DOI: 10.1016/j.apsusc.2019.02.128
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine adsorption on perfect and defective fcc nickel (100), (110) and (111) surfaces: A dispersion corrected DFT-D2 study

Abstract: We present density functional theory calculations, with a correction for the long-range interactions, of the adsorption of hydrazine (N2H4) on the Ni (110), (100), and (111) surfaces, both defect-free planes and surfaces containing point defects in the form of adatoms and vacancies. Several low-energy adsorption structures for hydrazine on the perfect and defective surfaces have been identified and compared. The hydrazine molecule is shown to interact with the Ni surfaces mainly through the lonepair of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The theoretical measurements suggested that the interaction between N 2 H 4 molecules and OH − ions was a mixture of direct chemical and electrostatic modes. The interaction of N 2 H 4 molecule with the Ni surfaces can be realized through a lone‐pair of electrons centered on N atoms, constructing either monodentate or bidentate bonding with the catalytic surface [88] . The configurations of adsorbed N 2 H 4 bounded to a low coordinate Ni atom with monodentate structure on the Ni 3 S 2 (110) surface have been examined by Liu and co‐workers [89] .…”
Section: An Overview Of Hzor Electrocatalysts: From Noble Metals To Nimentioning
confidence: 99%
See 4 more Smart Citations
“…The theoretical measurements suggested that the interaction between N 2 H 4 molecules and OH − ions was a mixture of direct chemical and electrostatic modes. The interaction of N 2 H 4 molecule with the Ni surfaces can be realized through a lone‐pair of electrons centered on N atoms, constructing either monodentate or bidentate bonding with the catalytic surface [88] . The configurations of adsorbed N 2 H 4 bounded to a low coordinate Ni atom with monodentate structure on the Ni 3 S 2 (110) surface have been examined by Liu and co‐workers [89] .…”
Section: An Overview Of Hzor Electrocatalysts: From Noble Metals To Nimentioning
confidence: 99%
“…The surface structure and porous texture would also play an important role contributing to ion diffusion and interface contact. Further, incorporating conductive counterparts and/or heteroatoms can endow catalysts with large surface areas and numerous active sites, which may render better enhancements in electrochemical activity [88,116] …”
Section: Basic Catalyst Formulation and Requirements For A Good Hzor mentioning
confidence: 99%
See 3 more Smart Citations